Employers social insurance contributions and employment - reply - Hughes, Gerard (Economic & Social Studies, 1986)
I do not accept Fagan ad Murphy's argument that my estimate of the employment effect is misleading. My estimate refers to the short run and it is, therefore, perfectly valid for the period to which it relates. The estimates of the long-run elasticity of demand for labour with respect to the real wage which have been produced recently are interesting as they suggest that the labour market in Ireland is more responsive to changes in the cost of labour than appeared to be the case in the past. However, the implications of these estimates for labour market policy need to be clarified for two reasons. The first is that it is the money demand elasticity which matters for practical purposes and the second is that we do not know how long it could take for the full effect of labour cost reductions to come through to employment.
Keywords: Employment - Ireland; Employers' Social Insurance Contributions